Factors Affecting Marketing Communications in Wartime - Ivan Lutsii; Oleksandr Lutsii (Облік і фінанси, 2024)
The company's choice of specific marketing tools and their combination depends on the goals set, the target audience's characteristics, the type of product being promoted, and the size of the budget. However, in crisis conditions caused by war, pandemic or natural disaster, the effectiveness of marketing communications is influenced by many more factors. The detailed analysis of such factors allows the company to adapt its marketing strategy to the realities of today. The article aims to reveal and systematize the factors affecting marketing communications in wartime conditions. It was found that the war changed companies' advertising policy, branding, and consumers' perceptions of goods and services. Therefore, to stay afloat, companies must study changes in the social climate on time and adapt their marketing strategies accordingly. Changing the nature and forms of communication with consumers plays a vital role in adapting marketing strategies. A consumer's attitude to specific brands and goods, based on the personal perception of the parties to the military conflict, is a sensitive factor in war conditions. Despite the general negative trend for business, the war opens up new opportunities for specific industries. In particular, using military themes in advertising can motivate the consumer to buy the company's products. However, one should be careful when using military symbols in advertising because the emotional perception of consumers can be different. Therefore, it is important to evaluate the negative consequences of war and understand how new opportunities can be used. The article systematizes the factors affecting marketing communications in wartime conditions and defines the measures that are an important component of business response to changes in market demand. The study results show that regardless of how effective the company's marketing strategy is in normal conditions, during the war, it needs to adapt to changes in the mood and habits of consumers and environmental factors.